Pendidikan Kesehatan Senam Hipertensi Untuk Menurunkan Tekanan Darah Pada Warga Bina Sosial Di Panti Sosial Tresna Werdha Budi Mulia 2 Jakarta Barat 2023 - Alfika Safitri; Mardiana pratiwi; Veronnicka Shintya Dewi; Nurul Fadhilah; Astuti Astuti; Devi Sri Rahayu; Siti Sopiah; Dede Nurjanah; Febiola Dwi Puspitasari; Sulyanti Suhartini; Lutfiah Galuh Ayu; Hilda Nuramaliyah; Luxiana Rahayu (Jurnal Rumpun Ilmu Kesehatan, 2023)
Hypertension is a conditional in which blood pressure increases beyond normal limits. Normal blood pressure varies according to age. All hypertension is a sport, one of which aims to incrase blood flow and oxygen supply to the active muscles and skeleton, especially to the heart muscle. The purpose of this hypertension exercise is to increase the knowledge of the elderly at the Tresna Werdha Budi Mulia 2. Social institution regarding hypertension exercise to reduce blood pressure. The method used is by socializing and providing counseling and displaying posters containing the steps in hypertension gymnastics. Health counseling was held on Thursday, june 8 2023. The population in this counseling were the elderly in Tresna Werdha Budi Mulia 2 Social institutions. After conducting health education about hypertension exercise, the results (100%) were that the elderly in Tresna Werdha Budi Mulia 2 Social institutions understood, understand and be able to give an example of how hypertension exercise to lower blood pressure.